Tratamiento de mejoramiento integral por medio de la integración de vacíos urbano al asentamiento brisas de oriente del municipio de Garzón Huila (2021)
This research is based on the growth of urban voids in the municipality of Garzón, currently identified within the PBOT and, from these, the Brisas de Oriente settlement is intervened; thus, taking into account that urban voids are areas without projection and that do not have a compatibility with the municipality, being occupied by urban settlements located in the periphery, this study does not have an urban planning, generating a deterioration of the environment. In this sense, in order to mitigate the environmental damage generated by this settlement, an articulation proposal is conceptualized, implementing aspects of sustainability for the community, involving it in the integration of urban voids through the treatment of the integral urban improvement of the municipality of Garzón (Huila).